Reflecting on appeals on questions of law arising out of domestic arbitration awards - CHAN, Darius (Institutional Knowledge at Singapore Management University, 2011)
Domestic arbitration awards rendered under the Arbitration Act (Cap 10, 2002 Rev Ed) (“the Act”) can be subject to appeal on a question of law arising out of an award. Unless parties consent, an appeal can only be brought with the leave of court.